Academic poster design at a national conference: a need for standardised guidance?. (7th December 2016) - Gopal, Alan; Redman, Melody; Cox, David; Foreman, David; Elsey, Elizabeth; Fleming, Simon
Summary: Background: Academic posters are a common means of disseminating information at conferences. Presentation at conferences is frequently given weight in postgraduate training programme recruitment. Some conferences provide guidance for visual presentation of posters. For the Association of the Study of Medical Education (ASME) Annual Scientific Meeting (ASM) 2015, poster abstract guidance was provided; however, the guidance on poster design was limited to size and orientation. The aim of this study was to investigate academic poster quality at a national medical education conference to identify where standards could be promoted and improved. Presentation at conferences is frequently given weight in postgraduate training programme recruitment Methods: Six auditors assessed all posters displayed at the ASME ASM (15–17 July 2015) using guidelines based upon a modified checklist for academic posters. Ten criteria were agreed as assessment standards for poster design quality. Results: One‐hundred‐and‐eighty posters were assessed: 29 per cent had appropriate copyright for the materials displayed ( n  = 52); 41 per cent included suitable contact details ( n  = 73); 48 per cent ( n  = 87) had a text to graphic ratio of 50 : 50; 72 per cent ( n  = 130) met ASME guidance for layout and orientation; 76 per cent ( n  = 137) had appropriate referencing; 78 per cent showed evidence of proofreading for grammar and spelling ( n  = 140); 79 per cent ( n  = 142) were readable at a distance of 2 metres; and 87 per cent used appropriate academic logos ( n  = 156). Discussion: There was variability in design quality as assessed by these criteria. We recommend that detailed guidance should be produced and disseminated by the organising conference. This may improve poster quality and aid in the communication of presented material. We aim to re‐audit following the production and dissemination of poster presentation guidance.